Impelementasi Konsep Maksim dalam Menilai Kejujuran Komunikasi Antara Dosen dan Mahasiswa - Muttaqin, Zainul; Wijaya, Herman; Taufiq, Muh. (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2018)
This research uses quantitative and qualitative descriptive methods. The objectives of the research are (a) to know what maxims are violated by students and lecturers of Hamzanwadi University in communicating, (b) explain the implementation of Maksim concept in assessing the honesty of Lecturer and Student  ommunication at Hamzanwadi University. The location of the research was conducted on the campus of Hamzanwadi University with the sample of research were 30 students and 3 lecturers. Data collection is done by using questionnaire, observation, and documentation. Data analysis techniques used in this study are descriptive statistics in the form of frequency distribution. The value of honesty data (beginning and end) is analyzed using T-Test type Paired Samples Test, while the data of honesty value using T-Test for each Independent Samples Test. Based on the research results found that the maxim is often violated by lecturers and students PGSD in the verbal stage of the maxim quality and maxim way. Based on the normality test the level of honesty of PGSD Student communication with 0.56 rerate categorized "quite honest" in class A, B da C at the interval of the suspension 0.30-0.70. Based on the questionnaire of honesty of lecturer of MKU BI teaching in PGSD found different level of honesty that is 66,67% elementary lecturer with index score interval of 0,67 which categorized "quite honest", then lecturer HY 80% with index intervalskor 0,80 which is categorized as "honest", and dose NE 73.33% with index score interval score of 0.73 which is "honest" with third rerate of lecturer is 73.33. Implementation of maxim concept of honesty value of communication between lecturers and students of PGSD on learning general course of Indonesia Language (BI) has fulfilled the principle of cooperation maxim with a fair degree of good honesty.Keywords: Implementation, Maxim, Honesty Value, Communication,